Multifunctional sandwich-structured magnetic-electric composite films with Joule heating capacities toward absorption-dominant electromagnetic interference shielding. (1st May 2022) - Guo, Zhengzheng; Ren, Penggang; Wang, Jin; Tang, Jiahui; Zhang, Fudong; Zong, Ze; Chen, Zhengyan; Jin, Yanling; Ren, Fang
Abstract: Exploring absorption-dominant high-efficiency electromagnetic interference (EMI) shielding composite films accompanied with additional functionalities to broaden their application scenarios is highly desirable for the development of next-generation electronic devices. In this regard, a sandwich-structured EMI shielding composite film with Joule heating performance was fabricated from biomass-based carbon and magnetic-electric hybrid materials through a feasible alternating vacuum-assisted filtration method. Profiting from the rational arrangement of Fe3 O4 @activated egg white/cellulose nanofiber as impedance matching layer and self-supported MXene as shielding layer, the resultant composite films achieve an optimum EMI shielding effectiveness (SE) of 63.8 dB in the X-band with an average electromagnetic reflection as low as 4.8 dB. Meanwhile, the prepared composite films present reliable EMI SE even after undergoing continuously physical deformations, outstanding flexibility, excellent mechanical property and remarkable Joule heating performance. This work paves a novel pathway for developing multifunctional and absorption-dominant EMI shielding composite films in advanced microelectronic systems and flexible electronic devices.